INTERACTIVE PHYSIC LEARNING MEDIA DESIGN USING LECTORA INSPIRE - atifah hirahmah; Silvi Yulia Sari; Hidayati Hidayati; Fanny Rahmatina Rahim (PILLAR OF PHYSICS EDUCATION, 2023)
The learning process in the digital era cannot be separated from information technology. Various kinds of applications are offered, ranging from paid to free. This study aims to describe the design of interactive learning media by utilizing a free application, namely Lectora Inspire. This application serves to make it easier for users to create interactive learning media designs. In addition, the Lectora Inspire application can assist teachers in the learning process with attractive and interactive media designs. Appropriate interactive learning media design can produce effectiveness in the learning process. In this case, this research is motivated by the use of learning media used in schools that are not fully interactive and are not in accordance with making good learning designs. For this reason, this study aims to design good interactive learning media by following the proper learning media design rules. The research method used in this research is research and development (R&D) with the ADDIE model namely analysis, design, development, implementation, and evaluation. Research on the development of the ADDIE model is limited to the early stages, namely Analysis and Design. From the results of the design of interactive learning media using the lectora inspire application developed by researchers, it is hoped that it will be useful for students and teachers at school so that students can master learning independently and have fun.